The role of Substance P in the defense line of the respiratory tract and neurological manifestations post COVID-19 infection - Mehboob, Riffat; Oehme, Peter; Pfaff, Gerhard (Frontiers in Neurology, 2023)
Substance P (SP) has been a great interest for scientists due to its unique properties and involvement in various physiological and pathological phenomenon. It took almost a century for the current understanding of this peptide so far. Its role in brain and gut were initially discussed and later on it was widely studied and observed in cardiovascular system, asthma, traumatic brain injury, immune response, vasodilation, behavior, inflammation, arthritis, cancer, airway hyper responsiveness and respiratory disorders. Involvement of SP in sudden perinatal death and COVID-19 has also been discussed which shed light on its vital role in respiratory rhythm regulation and initiation of cytokine storming in COVID-19. This article will provide a comprehensive overview of the researches done to understand the basic functions and involvement of SP in different processes of cell and its association with various diseases. This article describes the historical and scientific journey of SP from its discovery until today, including its future perspectives.